Isolation and structural characterization of cell wall polysaccharides from sesame kernel. (15th June 2022) - Liu, Xiao-Yan; Yu, Hai-Yang; Liu, Yi-Zhou; Qin, Zhao; Liu, Hua-Min; Ma, Yu-Xiang; Wang, Xue-De
Abstract: Cell wall polysaccharides from sesame kernel were extracted using sequential extraction method to obtained WSP, CSP, NSP, KSH-1, and KSH-4, respectively. In this study, the structures and properties of five polysaccharide fractions were analyzed. The results indicated that mannose was the predominant component monosaccharide in the WSP fraction, while arabinose was the predominant component monosaccharide in the other four. The molecular weights of five polysaccharide fractions ranged from 13270 to 811491 Da. Thermogravimetric analysis (TGA) showed that CSP had the best thermal stability. In terms of antioxidant activity, KSH-4 exhibited the highest DPPH radical scavenging activity with an EC50 value of 0.54 mg/mL, while CSP presented the highest DMPD + radical scavenging ability with an EC50 value of 1.45 mg/mL. This study can contribute to the development of sesame kernel processing by-products as functional food or feed. Highlights: The five cell wall polysaccharides were isolated from sesame kernel at first time. The structures of the five cell wall polysaccharides were analyzed. KSH-4 exhibited strong DPPH radical scavenging activity.